Medication Adherence Assessment and Cost Analysis of COPD Treatment Under Out-Patient Clinic in Vietnam - Thanh Thuy Phan; Van Giap Vu; Le-Thi; Viet Nhung Nguyen; Quy Chau Ngo (SAGE Publishing, 2023)
Chronic obstructive pulmonary disease (COPD) out-patient clinic is for stable patients but it requires patient's adherence to medicine and medical checkups. Our study aimed to assess COPD out-patient clinics management efficacy with respect to medication adherence and treatment costs at 3 out-patient clinics. Data were collected through 514 patient interviews and from medical records for statistical analysis. The most common comorbidity was hypertension (28.8%), and 52.9% of patients had experienced exacerbations in the past year requiring 75.7% of them to be hospitalized. According to the Morisky scale, 78.8% had high adherence and 82.9% were using inhaled corticosteroids regimens. The mean cost per year among different cohorts varied, with the out-patient cohort at $305.93, the acute exacerbations of COPD non-hospital cohort at $247.39, the standard admission cohort at $1275.3, and the emergency department cohort at $2132.5. Patients with low medication adherence had significantly lower annual costs ($238.25 vs $325.04, P  = .001). In Vietnam, economic constraints have made Inhaled corticosteroids/ Long-acting β-2 agonists the main mode of treatment. However, the exclusion of Long-acting β-2 agonists/Long-acting anti-muscarinic antagonists drugs from health insurance coverage poses a challenge to Global Initiative for Chronic Obstructive Lung Disease-based prescription practices and increases the importance of monitoring medication adherence, particularly in patients with higher COPD Assessment Test scores.